Asbestos and Probable Microscopic Polyangiitis. Issue 5 (3rd August 2004) - Philteos, George S Rashed; Coverett, Kelly; Chibbar, Rajni; Ward, Heather A; Cockcroft, Donald W
Abstract : Several inorganic dust lung diseases (pneumoconioses) are associated with autoimmune diseases. Although autoimmune serological abnormalities are common in asbestosis, clinical autoimmune/collagen vascular diseases are not commonly reported. A case of pulmonary asbestosis complicated by perinuclear-antineutrophil cytoplasmic antibody (myeloperoxidase) positive probable microscopic polyangiitis (glomerulonephritis, pericarditis, alveolitis, multineuritis multiplex) is described and the possible immunological mechanisms whereby asbestosis fibres might be relevant in induction of antineutrophil cytoplasmic antibodies are reviewed in the present report.